Study on spatial evolution and mechanism of county economic differences in Hubei province from 2005 to 2020 - Jiang, Liang; Chen, Jie; Zhang, Chunyan; Tian, Ye; Wu, Guoxi; Luo, Jing (Frontiers in Earth Science, 2022)
he spatial distribution pattern of the economic development among counties is an important external representation of a balanced and sustainable regional development in China. With the rapid development of globalization and localization, spatial pattern of economic growth is increasingly obvious. The mechanisms of regional economic growth in China are also gradually gaining attention. However, there is still a lack of research at the province and county levels. As a result, based on the per capita GDP of each county in Hubei Province from 2005 to 2020 as the research index, the spatial autocorrelation and the spatial variation function are used to analyze the spatial pattern evolution and the county economy mechanism in Hubei Province. The results show that: (1) there is a remarkable phenomenon of county-level economic spatial agglomeration in Hubei Province. The urban area of Wuhan and its surrounding counties are High-High(HH-type) county agglomeration areas. The Low-Low (LL-type) counties are mainly distributed in the western parts of Hubei Province, and scattered in the northeastern and southern parts of Hubei Province. (2) The county economy of Hubei Province presents a spatial distribution pattern of "high in the east and low in the west". The hot areas of the county economy are primarily located in the urban area of Wuhan and its surrounding areas. In the process of development, the hot spot areas tend to shift to Yichang, Jingmen and Xiangyang. The cold spot areas are located on the edges of the western, northeastern and southeastern areas of Hubei Province. (3) The spatial continuity and self-organization of the county economic development are strengthened. The structural differentiation trend caused by spatial autocorrelation is also strengthened. The county economy is relatively balanced from the southeast to the northwest, and the spatial difference in economic development in other directions is increasing. (4) The spatial evolution of county economic development in Hubei province is the result of the comprehensive effects of historical and cultural background, economic development, traffic location and policy system, and the A-shaped point-axis structure is a reliable spatial structure for regional development in Hubei Province.